Incorporation of cerium oxide in hollow mesoporous bioglass scaffolds for enhanced bone regeneration by activating the ERK signaling pathway. (28th March 2019) - Lu, Bin; Zhu, Dao-Yu; Yin, Jun-Hui; Xu, He; Zhang, Chang-Qing; Ke, Qin-Fei; Gao, You-Shui; Guo, Ya-Ping
Abstract: Hierarchically porous structures and bioactive compositions of artificial biomaterials play a positive role in bone defect healing and new bone regeneration. Herein, cerium oxide nanoparticles-modified bioglass (Ce-BG) scaffolds were firstly constructed by the incorporation of hollow mesoporous Ce-BG microspheres in CTS via a freeze-drying technology. The interconnected macropores in Ce-BG scaffolds facilitated the in-growth of bone cells/tissues from material surfaces into the interiors, while the hollow cores and mesopore shells in Ce-BG microspheres provides more active sites for bone mineralization. The cerium oxide nanoparticles in the scaffolds rapidly promoted the proliferation and osteogenic differentiation of human bone marrow-derived mesenchymal stem cells (hBMSCs), as confirmed by the up-regulation of osteogenesis-related markers such as OCN, ALP and COL-1. The enhanced osteoinductivity of Ce-BG scaffolds was mainly related to the activated ERK pathway, and it was blocked by adding a selective ERK1/2 inhibitor (SCH772984). In vivo rat cranial defect models revealed that Ce-BG scaffolds accelerated collagen deposition, osteoblast formation and bone regeneration as compared to BG scaffolds. The exciting results demonstrated that the synergistic effects between hierarchically porous structures and cerium oxide nanoparticles contributed to osteogenic ability, and hollow mesoporous Ce-BG scaffolds would be a novel platform for bone regeneration.